Prevalence of the use of anorexigenic drugs by academics of a private institution at Montes Claros-MG - Diego Pitangui Guedes de OLIVEIRA; Lucas Thadeu Rodrigues LAGES; Jadson Rabelo ASSIS (Federal Council of Pharmacy, 2013)
Every day there are growing difficulties in maintaining a healthy lifestyle, obesity is becoming more common and it is considered a public health problem reaching worldwide levels. Besides, there is the pressure of society and the media for a slim look, and all these factors have led to an overuse of anorectics drugs with purely aesthetic purpose, without concerns for the danger of uncontrolled use. Thus, this study aimed to assess the prevalence of use of anorectics among scholars of both sexes enrolled at the first period of the courses in the area of health in a private institution of higher education in the city of Montes Claros - MG. We applied 123 questionnaires containing 11 questions to Pharmacy, Medicine, Physiotherapy, Nursing and Psychology students. Of this total, 82.9% (n = 102) were females and 17.1% (n = 21) were male. There was a consumption of anorectics only among females of 8.1%, and Sibutramine and Fluoxetine are the most consumed drugs. The most common side effects were restlessness (80%) and anxiety (70%). Regarding the reason of use, 50% of the students claimed to have used such drugs for aesthetics purpose, 40% because overweight condition and 10% for both reasons. The results show a dangerous tendency to ignore the adverse effects of anorectics, even among people who study the field of health, which can bring many problems to users.